PictoEZodit / Khair Syakira Bustamam … [et al.] - Bustamam, Khair Syakira; Mamat, Siti Nurulhuda; Saidin, Amilia; Adanan, Siti Azrina; Abdullah Sani, A'ieshah; Abd Samad, Khairunnisa (Faculty of Computer and Mathematical Sciences, 2021)
Learning auditing as a theory subject for accounting students can be very dull and mundane. The audit theory is commonly memorized by students from textbooks which is textual and challenging for the students to apply into real case scenarios. However the students have not yet been exposed to the audit working environment, hence lack knowledge of how to apply audit theory in practice. As a result, PictoEZodit was created as an interactive educational tool to address this issue. This “comic strip” makes use of visual images mostly pictorial as a learning tool and designed to be used in both offline and online classrooms. As such, PictoEZodit intended to create harmony between theoretical learning and the real working environment of auditing practices.